Don't worry, be happy? Happiness and reemployment - Annabelle Krause (Institute for the Study of Labor (IZA), 2012)
Subjective well-being is primarily treated as an outcome variable in the economic literature. However, is happiness also a driver of behavior and life's outcomes? Rich survey data of recent entrants into unemployment in Germany show that a significant inverted U-shaped relationship exists between residual happiness and an unemployed individual's future reemployment probability and the reentry wage. Residual life satisfaction displays higher (or lower) satisfaction levels than would be predicted by a number of socioeconomic and demographic characteristics. This paper is the first to show that happiness is mainly a predictor for self-employment and less for standard reemployment. Related findings suggest that happiness matters for male unemployed, and the concept of locus of control is able to explain part of the effect. If reemployment and higher wages are considered desirable outcomes for the unemployed individual and society, the shape of the effect suggests an optimal level of happiness, which is not necessarily the highest.
Keywords: J60; J64; I31; 330; unemployment; job search; happiness; reemployment; Germany; Zufriedenheit; Arbeitslosigkeit; Arbeitsuche; Berufliche Integration; Schätzung; Deutschland